Development of a tool to routinely monitor wastewater systems via non-target screening utilizing spatial fingerprinting and temporal trend analysis as prioritization techniques - Reyhaneh Armin; Gerrit Renner; Markus Weber; Torsten C. Schmidt (Journal of Environmental Management, 2025)

Projected changes in seasonal and monthly atmospheric near-surface parameters over West Africa from simulations of CORDEX-CORE ensemble - Andre Lenouo; Torsten Weber; Alain T. Tamoffo; Peter Hoffmann; Gaby S. Langendijk; Carine Betant; Alphonse Um Um; Cyrille Meukaleuni; Eric Efon; Rinelle Djiondo Ngongang (Modeling Earth Systems and Environment, 2025)

Association of cardiorespiratory fitness level with vascular function and subclinical atherosclerosis in the elderly - Vincent Größer; Christopher Weyh; Tim Böttrich; Torsten Frech; Svenja Nolte; Natascha Sommer; Magdalena Huber; Klaus Eder; Oliver Dörr; Sophie Hoelscher; Rebecca Weber; Ebru Akdogan; et al. (European Journal of Applied Physiology, 2024)
Purpose Physical exercise is crucial for healthy aging and plays a decisive role in the prevention of atherosclerotic cardiovascular disease (ASCVD). A higher level of cardiorespiratory fitness (CRF) in the elderly is associated with lower cardiovascular and all-cause mortality. This study investigated the association of CRF level with vascular function and cardiovascular risk factors in the elderly. Methods We examined 79 apparently healthy and physically active subjects aged > 55 years (64 ± 4 years). Cardiovascular functional parameters assessed included brachial and central blood pressure (BP), pulse wave velocity (PWV), augmentation index (Aix), and ankle-brachial index. Sonography of the common carotid artery was performed. CRF level was determined by a cardiopulmonary exercise test, and everyday activity was quantified with an accelerometer. Results All participants had a higher CRF level than the reported age-specific normative values. Twenty-nine subjects had subclinical atherosclerosis of the common carotid artery. Compared with participants without atherosclerosis, they were older ( p = 0.007), displayed higher brachial systolic BP ( p = 0.006), and higher central systolic BP ( p = 0.014). Lower brachial ( p = 0.036) and central ( p = 0.003) systolic BP, lower PWV ( p = 0.004), lower Aix ( p < 0.001), lower body fat percentage (< 0.001), and lower LDL cholesterol ( p = 0.005) were associated with a higher CRF level. Conclusions In this cohort of healthy and physically active individuals, subjects with subclinical atherosclerosis displayed higher systolic brachial and central BP. A higher CRF level was associated with enhanced vascular function, consistent with an influence of CRF on both BP and vascular function in the elderly.

Robustness of climate indices relevant for agriculture in Africa deduced from GCMs and RCMs against reanalysis and gridded observations - Daniel Abel; Katrin Ziegler; Imoleayo Ezekiel Gbode; Torsten Weber; Vincent O. Ajayi; Seydou B. Traoré; Heiko Paeth (Climate Dynamics, 2024)
This study assesses the ability of climate models to represent rainy season (RS) dependent climate indices relevant for agriculture and crop-specific agricultural indices in eleven African subregions. For this, we analyze model ensembles build from Regional Climate Models (RCMs) from CORDEX-CORE (RCM_hist) and their respective driving General Circulation Models (GCMs) from CMIP5 (GCM_hist). Those are compared with gridded reference data including reanalyses at high spatio-temporal resolution (≤ 0.25°, daily) over the climatological period 1981–2010. Furthermore, the ensemble of RCM-evaluation runs forced by ERA-Interim (RCM_eval) is considered. Beside precipitation indices like the precipitation sum or number of rainy days annually and during the RS, we examine three agricultural indices (crop water need (CWN), irrigation requirement, water availability), depending on the RS’ onset. The agricultural-relevant indices as simulated by climate models, including CORDEX-CORE, are assessed for the first time over several African subregions. All model ensembles simulate the general precipitation characteristics well. However, their performance strongly depends on the subregion. We show that the models can represent the RS in subregions with one RS adequately yet struggle in reproducing characteristics of two RSs. Precipitation indices based on the RS also show variable errors among the models and subregions. The representation of CWN is affected by the model family (GCM, RCM) and the forcing data (GCM, ERA-Interim). Nevertheless, the too coarse resolution of the GCMs hinders the representation of such specific indices as they are not able to consider land surface features and related processes of smaller scale. Additionally, the daily scale and the usage of complex variables (e.g., surface latent heat flux for CWN) and related preconditions (e.g., RS-onset and its spatial representation) add uncertainty to the index calculation. Mostly, the RCMs show a higher skill in representing the indices and add value to their forcing models.

Understanding the diversity of the West African monsoon system change projected by CORDEX-CORE regional climate models - Alain T. Tamoffo; Akintomide A. Akinsanola; Torsten Weber (Climate Dynamics, 2023)

Process-oriented evaluation of the West African Monsoon system in CORDEX-CORE regional climate models - Alain T. Tamoffo; Alessandro Dosio; Leonard K. Amekudzi; Torsten Weber (Climate Dynamics, 2023)

Benefits of simulating precipitation characteristics over Africa with a regionally-coupled atmosphere–ocean model - Torsten Weber; William Cabos; Dmitry V. Sein; Daniela Jacob (Climate Dynamics, 2023)
High-quality climate information at appropriate spatial and temporal resolution is essential to develop and provide tailored climate services for Africa. A common method to produce regional climate change data is to dynamically downscale global climate projections by means of regional climate models (RCMs). Deficiencies in the representation of the sea surface temperatures (SSTs) in earth system models (ESMs) and missing atmosphere–ocean interactions in RCMs contribute to the precipitation bias. This study analyzes the influence of the regional atmosphere–ocean coupling on simulated precipitation and its characteristics over Africa, and identifies those regions providing an added value using the regionally coupled atmosphere–ocean model ROM. For the analysis, the MPI-ESM-LR historical simulation and emission scenario RCP8.5 were dynamically downscaled with ROM at a spatial resolution of 0.22° × 0.22° for the whole African continent, including the tropical Atlantic and the Southwest Indian Ocean. The results show that reduced SST warm biases in both oceans lead to more realistic simulated precipitation over most coastal regions of Sub-Saharan Africa and over southern Africa to varying degrees depending on the season. In particular, the annual precipitation cycles over the coastal regions of the Atlantic Ocean are closer to observations. Moreover, total precipitation and extreme precipitation indices in the coupled historical simulation are significantly lower and more realistic compared to observations over the majority of the analyzed sub-regions. Finally, atmosphere–ocean coupling can amplify or attenuate climate change signals from precipitation indices or even change their sign in a regional climate projection.

Climate hazard indices projections based on CORDEX-CORE, CMIP5 and CMIP6 ensemble - Erika Coppola; Francesca Raffaele; Filippo Giorgi; Graziano Giuliani; Gao Xuejie; James M. Ciarlo; Taleena Rae Sines; José Abraham Torres-Alavez; Sushant Das; Fabio di Sante; Emanuela Pichelli; Russell Glazer; et al. (Climate Dynamics, 2021)

Assessing mean climate change signals in the global CORDEX-CORE ensemble - Claas Teichmann; Daniela Jacob; Armelle Reca Remedio; Thomas Remke; Lars Buntemeyer; Peter Hoffmann; Arne Kriegsmann; Ludwig Lierhammer; Katharina Bülow; Torsten Weber; Kevin Sieck; Diana Rechid; et al. (Climate Dynamics, 2021)
The new Coordinated Output for Regional Evaluations (CORDEX-CORE) ensemble provides high-resolution, consistent regional climate change projections for the major inhabited areas of the world. It serves as a solid scientific basis for further research related to vulnerability, impact, adaptation and climate services in addition to existing CORDEX simulations. The aim of this study is to investigate and document the climate change information provided by the CORDEX-CORE simulation ensemble, as a part of the World Climate Research Programme (WCRP) CORDEX community. An overview of the annual and monthly mean climate change information in selected regions in different CORDEX domains is presented for temperature and precipitation, providing the foundation for detailed follow-up studies and applications. Initially, two regional climate models (RCMs), REMO and RegCM were used to downscale global climate model output. The driving simulations by AR5 global climate models (AR5-GCMs) were selected to cover the spread of high, medium, and low equilibrium climate sensitivity at a global scale. The CORDEX-CORE ensemble has doubled the spatial resolution compared to the previously existing CORDEX simulations in most of the regions (25 $$\,km$$ km (0.22 $$^{° }$$ ∘ ) versus 50 $$\,km$$ km (0.44 $$^{° }$$ ∘ )) leading to a potentially improved representation of, e.g., physical processes in the RCMs. The analysis focuses on changes in the IPCC physical climate reference regions. The results show a general reasonable representation of the spread of the temperature and precipitation climate change signals of the AR5-GCMs by the CORDEX-CORE simulations in the investigated regions in all CORDEX domains by mostly covering the AR5 interquartile range of climate change signals. The simulated CORDEX-CORE monthly climate change signals mostly follow the AR5-GCMs, although for specific regions they show a different change in the course of the year compared to the AR5-GCMs, especially for RCP8.5, which needs to be investigated further in region specific process studies.

A new spatially distributed added value index for regional climate models: the EURO-CORDEX and the CORDEX-CORE highest resolution ensembles - James M. Ciarlo`; Erika Coppola; Adriano Fantini; Filippo Giorgi; XueJie Gao; Yao Tong; Russell H. Glazer; Jose Abraham Torres Alavez; Taleena Sines; Emanuela Pichelli; Francesca Raffaele; Sushant Das; et al. (Climate Dynamics, 2021)

Sensitivity of the atmospheric water cycle to corrections of the sea surface temperature bias over southern Africa in a regional climate model - Torsten Weber; Andreas Haensler; Daniela Jacob (Climate Dynamics, 2018)

The Ty1-copia families SALIRE and Cotzilla populating the Beta vulgaris genome show remarkable differences in abundance, chromosomal distribution, and age - Beatrice Weber; Torsten Wenke; Ulrike Frömmel; Thomas Schmidt; Tony Heitkam (Chromosome Research, 2010)

A BAC library of Beta vulgaris L. for the targeted isolation of centromeric DNA and molecular cytogenetics of Beta species - Gunnar Jacobs; Daryna Dechyeva; Torsten Wenke; Beatrice Weber; Thomas Schmidt (Genetica, 2009)